The best american science fiction and fantasy 2022 eaudiobook - Adams, John Joseph (Best American Science Fiction and Fantasy., 2022)
Award-winning, New York Times bestselling author and guest editor Rebecca Roanhorse and series editor John Joseph Adams select twenty pieces that represent the best examples of the form published the previous year and explore the ever-expanding and changing world of SFF today. Today's readers of science fiction and fantasy have an appetite for stories that address a wide variety of voices, perspectives, and styles. There is an openness to experiment and pushing boundaries, combined with the classic desire to read about spaceships and dragons, future technology and ancient magic, and the places where they intersect. Contemporary science fiction and fantasy looks to accomplish the same goal as ever—to illuminate what it means to be human. With a diverse selection of stories chosen by series editor John Joseph Adams and guest editor Rebecca Roanhorse, The Best American Science Fiction and Fantasy 2022 explores the ever-expanding and changing world of contemporary science fiction and fantasy. Supplemental enhancement PDF accompanies the audiobook.